New Technological Solutions, Research Methods, Simulation and Analytical Models That Support the Development of Modern Transport Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The sustainable development of transport systems (including eco-mobility, energy efficiency, reduction of CO2 emissions and noise emissions), digital transformation of transport processes, and development of information technology have generated an increasing demand for scientific research to support managerial and engineering decisions linked to improving current transport systems and processes. For this reason, research studies with results that can be implemented in real transport systems are becoming increasingly valuable. The development of cyber–physical systems provides an increasing amount of data, which requires complex models and methods developed by the scientific community to be analyzed and correctly interpreted. On the other hand, technology supports science in terms of the analytical tools used and the methods of improving professional competencies. The Topic aims to present new technological solutions, research methods, and analytical models that support the development of modern transport systems (considering the requirements of passengers, freight, and urban transport). All modes of transport are undergoing fundamental technological, organizational, and infrastructural changes. For this reason, this Topic is also focused on presenting new approaches to the ongoing changes and solutions regarding the functioning of transport systems. The key aspect here is the development of methods for building the resistance of transport systems to withstand emerging disturbances and threats. All methods and approaches are welcome, including reliability and risk assessment, as well as analytical and simulation modelling.